2018
DOI: 10.1038/s41598-018-22172-5
|View full text |Cite
|
Sign up to set email alerts
|

Target delivery of doxorubicin tethered with PVP stabilized gold nanoparticles for effective treatment of lung cancer

Abstract: Development of drug delivery system conjugated with doxorubicin (dox) on the surface of AuNPs with polyvinylpyrrolidone (Dox@PVP-AuNPs), we have demonstrated that human lung cancer cells can significantly overcome by the combination of highly effective cellular entry and responsive intracellular release of doxorubicin from Dox@PVP-AuNPs complex. Previously drug release from doxorubicin-conjugated AuNPs was confirmed by the recovered fluorescence of doxorubicin from quenching due to the nanosurface energy trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(63 citation statements)
references
References 58 publications
1
61
0
1
Order By: Relevance
“…Doxorubicin was selected to evaluate the ability of these nanoparticles to encapsulate bioactive substances. DOX, an antibiotic of the anthracycline family, is a front‐line drug used clinically to treat different tumors such as liver or lung cancer . However, DOX has a narrow therapeutic index for clinical use because of its side effects, such as cardiotoxicity and myelosuppression.…”
Section: Resultsmentioning
confidence: 99%
“…Doxorubicin was selected to evaluate the ability of these nanoparticles to encapsulate bioactive substances. DOX, an antibiotic of the anthracycline family, is a front‐line drug used clinically to treat different tumors such as liver or lung cancer . However, DOX has a narrow therapeutic index for clinical use because of its side effects, such as cardiotoxicity and myelosuppression.…”
Section: Resultsmentioning
confidence: 99%
“…1C, D). This result suggested that the size of GRs have increased up to around 100 nm by conjugation of resveratrol to GNPs via PVP [19,20]. Gangwar et al described that curcumin was conjugated via PVP to gold nanoparticle through intermolecular hydrogen bonding to enolic hydroxyl group [19].…”
Section: Gnps Synthesismentioning
confidence: 97%
“…In addition, DOX@PVP-Au-NPs highly upregulated tumor suppressor gene expression compared with DOX and PVP-Au-NPs and induced intrinsic apoptosis in lung cancer cells. 55 DOX shows a cumulative dose-dependent side effect of cardiotoxicity. Du et al designed an Au-NP-based DDS to solve this problem.…”
Section: Dox Delivery By Au-npsmentioning
confidence: 99%